Exploring Slavery Practices in 19th Century Bengal: Insights from Two Unpublished Human Sale Deeds at the Bangladesh National Museum - Md. Sanaullah; Md. Abdul Muhit; Rudra Prosad Samaddar; Md Jowel Rana (Indonesian Academy of Social and Religious Research (IASRR), 2025)
This study explores the historical significance of two unpublished human sale deeds, dated 1214 and 1215 (1807-1808 AD), preserved in the Bangladesh National Museum. Collected in 1980 AD from Mymensingh District of Bangladesh, they provide significant insight into the practice of self-slavery in Bengal during the early 19th century under British colonial rule. Written in Bengali and Sanskrit using the 19th century Proto-Bengali script, these deeds reveal the dire socio-economic conditions that compelled individuals to sell themselves or their family members into servitude in exchange for basic necessities such as food, clothing, and minimal monetary price. Employing a qualitative research approach, this study integrates document analysis, translation, and historical contextualization to interpret the texts and explore their legal, socio-economic, and cultural implications. The findings indicate that the devastating consequences of the Famine of 1770, the exploitative revenue system formed by the Permanent Settlement of 1793, and deep-rooted inequalities within rural society contributed to an environment in 19th century Bengal where survival often necessitated the forfeiture of personal freedom. By situating these findings within the broader context of global discussions on slavery, the research challenges the dominant colonial narratives of progress and highlights the inequality and labor exploitation in contemporary society.